MENUJU ELIMINASI TUBERKULOSIS (PADA ANAK) DI INDONESIA PADA TAHUN 2030: SEBUAH TINJAUAN - Meiriani Sari; Firda Fairuza; Dita Setiati; Nathalia Ningrum; Nia Nurul Aziza (Jurnal Akta Trimedika, 2024)
Based on WHO (World Health Organization) data in November 2023, Indonesia was still ranked in the top two cases of Tuberculosis (TB) in the world. The increase in patients with resistance to Anti Tuberculosis Drugs (ATD) available in Indonesia was increasing. TB infections not only happened in adults but children were also a group that was vulnerable to TB infection. The central and regional government had prepared various strategies to archive the elimination of TB in Indonesia by 2030.The strategies that had been prepared by the Indonesian government require support from the entire community, especially health workers. Exposed to TB elimination program had been carried out by both central and regional governments. Various trainings regarding the recognition of TB disease, therapy and programs to increase TB detection had been held by the government. How ever not all levels of society, even health worker, were exposed to this TB elimination program. Until 2024 the TB elimination program is still focused on increasing the number of TB cases detection. This shows that strong efforts from the government are still needed to achieve TB elimination. The government need to be more aggressive in disseminating information about TB elimination programs through mass media, conducting seminars or training for health workers and the community. It is hoped that this action can increase case findings and cure rate of TB by as much as 90 percent so the incidence of infection can decrease significantly in the next couple years.